Beta-Catenin and Estrogen Signaling Collaborate to Drive Cyclin D1 Expression in Developing Mouse Prostate - Mulligan, William A. (Differentiation, 2016)
Androgen, beta-catenin (CTNNB1), and estrogen pathways stimulate proliferative growth of developing mouse prostate but how these pathways interact is not fully understood. We previously found that androgens induce CTNNB1 signaling in mouse urogenital sinus (UGS) epithelium from which prostatic ductal epithelium derives. Others have shown that low estradiol concentrations induce UGS epithelial proliferative growth. Here, we found that CTNNB1 signaling overlaps cyclin D1 (CCND1) expression in prostatic buds and we used a genetic approach to test whether CTNNB1 signaling induces CCND1 expression. We observed an unexpected sexually dimorphic response to hyperactive CCNTB1 signaling: in male mouse UGS it increased Ccnd1 mRNA abundance without increasing its protein abundance but in female UGS it increased Ccnd1 mRNA and protein abundance, suggesting a potential role for estrogens in stabilizing CCND1 protein. Treating wild type male UGS explants with androgen and either 17β-estradiol or a proteasome inhibitor increased CCND1 protein and KI67 labeling in prostatic bud epithelium. Together, our results are consistent with an epithelial proliferative growth mechanism linking CTNNB1-driven Ccnd1 transcription and estrogen-mediated CCND1 protein stabilization.